Formation of Zr- oxynitride thin films on 4H-SiC substrate - Wong, Y.H.; Cheong, K.Y. (Elsevier, 2012)
Formation of Zr-oxynitride by simultaneous oxidation and nitridation in nitrous oxide of sputtered Zr on SiC substrate is reported. Sputtered Zr on SiC substrate and followed by oxidation and nitridation in nitrous oxide ambient for 15 min at different temperatures (400–900 °C) have been systematically investigated. By using X-ray photoelectron spectroscopy, chemical compositions, and depth profile analysis have been evaluated, as well as energy band alignment of Zr-oxynitride/interfacial layer/SiC system. Zr-oxynitride film of Zr–O, Zr–N, and/or Zr–O–N and its interfacial layer composed of mixed Zr–O, Zr–N, Zr–O–N, Zr–Si–O, Si–N, and/or C–N phases were verified. A possible model related to the oxidation and nitridation mechanisms has been proposed and explicated.